On the impact of flax fibers as an internal layer on the properties of basalt-epoxy composites modified with silanized basalt powder. (August 2020) - Matykiewicz, Danuta; Barczewski, Mateusz
Abstract: The main aim of this study was to evaluate the thermomechanical properties of hybrid epoxy composites reinforced with flax and basalt fiber and modified with silanized basalt powder as materials with a high content of natural ingredients. The structure of the composites was investigated with scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR). Moreover, thermogravimetric analysis (TGA) in inert and oxidizing atmospheres, dynamic mechanical thermal analysis (DMTA), tensile and flexural tests and impact tests of the composites were conducted. It was found that the incorporation of silanized basalt powder into the epoxy matrix improved the thermomechanical properties of the composites. Moreover, incorporating flax fibers as an internal reinforcement layer does not negatively affect the mechanical properties of the epoxy composites reinforced with basalt fabric. Highlights: Incorporating flax fibers as an internal reinforcement layer does not negatively affect the mechanical properties of the epoxy composites reinforced with basalt fabric. The introduction of silanized basalt into the epoxy matrix improved the thermomechanical properties as well as stiffness of the composites.